Răspuns :
Răspuns:
Explicație pas cu pas:
[( x - 8 ) : 4 + 5 ] × 5 +5 = 110
Folosim metoda mersului invers
[ ( x - 8 ):4+5 ] × 5 = 110 - 5
[ ( x - 8 ) : 4 + 5 ] × 5 = 105
( x - 8 ) : 4 + 5 = 105 : 5
( x - 8 ) : 4 +5 = 21
( x - 8 ) : 4 = 21 - 5
( x - 8 ) : 4 = 16
x - 8 = 16 × 4
x - 8 = 64
x = 64 + 8
x = 72
{ [ ( x - 8 ) : 4 ] + 5 } × 5 + 5 = 110
{ [ ( x - 8 ) : 4 ] + 5 } × 5 = 110 - 5
{ [ ( x - 8 ) : 4 ] + 5 } × 5 = 105
[ ( x - 8 ) : 4 ] + 5 = 105 : 5
[ ( x - 8 ) : 4 ] + 5 = 21
( x - 8 ) : 4 = 21 - 5
( x - 8 ) : 4 = 16
x - 8 = 16 × 4
x - 8 = 64
x = 64 + 8
x = 72